Analysis of monocyte-derived dendritic cells obtained through conventional vs. fast differentiation/maturation protocols - Mendes, Cátia da Silva (2021)
Dendritic cells (DCs) are cells specialized in antigen presentation that play an important role in the connection between innate and adaptive immunity. These cells have the unique ability to recognize, capture, process and present antigens to naïve T cells, leading to their polarization in different effector populations. Because of this ability, DCs have been used in recent decades to develop cancer immunotherapy approaches. In this type of cellular immunotherapy, the production of ex vivo DCs is necessary, and there are several protocols for this purpose. The aim of the present work was to compare two differentiation protocols, Fast (1 day) and Conventional (6 days), while four different maturation cocktails were also tested, where samples from 8 healthy donors were used. For this comparison, the immunophenotypic profile, uptake capacity, cytokine production and metabolic activity were assessed. The results showed that, despite some differences, the cells differentiated by the Fast protocol had a phenotypic profile and uptake capacity very similar to Conventional DCs. Regarding the response to the different maturation conditions, both Fast and Conventional CDs matured more effectively when stimulated with the Alpha cocktail or TLR ligands. At the metabolic level, the main differences between protocols were related to the higher glycolytic and/or glutaminolytic activity of the cells differentiated by the Conventional method. In terms of maturation, the Alpha cocktail appeared to stimulate glutaminolysis, while maturation with the Standard cocktail appeared to favor glycolysis.